2009
DOI: 10.3324/haematol.2009.008318
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D gene polymorphism has a significant impact on transplant outcomes after HLA-fully-matched unrelated bone marrow transplantation for standard risk hematologic malignancies

Abstract: BackgroundNKG2D, an activating and co-stimulatory receptor expressed on natural killer cells and T cells, plays pivotal roles in immunity to microbial infections as well as in cancer immunosurveillance. This study examined the impact of donor and recipient polymorphisms in the NKG2D gene on the clinical outcomes of patients undergoing allogeneic T-cell-replete myeloablative bone marrow transplantation using an HLA-matched unrelated donor. Design and MethodsThe NKG2D polymorphism was retrospectively analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 40 publications
2
61
4
2
Order By: Relevance
“…Current evidence suggests that in addition to HLA matching, genetic diversity among donors and recipients, including cytokine genes, innate immunity genes and pharmacogenetic polymorphisms, affect the success of transplantation by regulating alloimmune responses. [2][3][4][5] Optimal donor T lymphocyte proliferation, differentiation and acquisition of effector functions play a critical role in alloimmune reactivity, and their ability to detect non-self-antigens can lead to GVHD or contribute to the prevention of relapse and infections after transplantation. CD28, inducible co-stimulator (ICOS) and cytotoxic Tlymphocyte antigen 4 (CTLA-4) belong to the same family of T-cell co-stimulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that in addition to HLA matching, genetic diversity among donors and recipients, including cytokine genes, innate immunity genes and pharmacogenetic polymorphisms, affect the success of transplantation by regulating alloimmune responses. [2][3][4][5] Optimal donor T lymphocyte proliferation, differentiation and acquisition of effector functions play a critical role in alloimmune reactivity, and their ability to detect non-self-antigens can lead to GVHD or contribute to the prevention of relapse and infections after transplantation. CD28, inducible co-stimulator (ICOS) and cytotoxic Tlymphocyte antigen 4 (CTLA-4) belong to the same family of T-cell co-stimulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs) that effect individual immune response to infections and inflammatory reactions are associated with transplant outcomes. [3][4][5][6][7][8][9] Fcg receptor type IIIA (FCGR3A), a low-affinity receptor capable of interaction with complexed or monomeric IgG, is expressed on neutrophils, eosinophils, natural killer cells, macrophages, monocytes, DC, gd-positive T cells and keratinocytes. [10][11][12][13] FCGR3A mediates Ab-dependent cell-mediated cytotoxicity, phagocytosis, cytokine production and regulation of Ig production.…”
Section: Introductionmentioning
confidence: 99%